P171 Impact of a novel high-definition tDCS set-up on cognitive control. Issue 3 (March 2017) - Gbadeyan, O.; Steinhauser, M.; McMahon, K.; Hsieh, B.; Meinzer, M.
Abstract : Question: High-definition transcranial direct current stimulation (HD-tDCS) allows for more focal current delivery than conventional-tDCS. However, very few studies have assessed potential cognitive effects and regional specificity of HD-tDCS. Objectives: This study assessed the impact and specificity of a novel HD-tDCS montage on cognitive control during a visual flanker task. Methods: 120 healthy young participants were recruited and randomly assigned to four stimulation conditions: left or right dorsolateral prefrontal cortex (DLPFC) or primary motor cortex (M1) HD-tDCS ( N  = 30 per condition). Each group underwent both active- and sham HD-tDCS in cross-over, double-blind designs. tDCS was administered using a one-channel DC-stimulator and two concentric round rubber electrodes mimicking the frequently used "4 × 1" HD-tDCS set-up. Our analyses focused on conflict adaptation (CA), a hallmark effect of adaptive cognitive control. Conflict adaptation in the flanker paradigm is reflected by the finding that the flanker effect (i.e., differences in response latency between incongruent and congruent trials in the flanker task) is smaller following trials with high vs. low response conflict. Results: We obtained a sizeable CA effect which was influenced by region-specific active HD-tDCS, as indicated by a significant four-way interaction between region, stimulation, current congruency and previous congruency ( p  < 0.05). In the DLPFC groups, a significant three-way interaction between stimulation, current congruency and previous congruency ( p  < 0.003) indicated larger conflict adaptation during active- vs. sham HD-tDCS. This effect was not further modulated by the laterality of the stimulation. In the M1 groups, CA was not modulated by HD-tDCS. However, we obtained trends suggesting that M1 stimulation led to activation of the contralateral hand but these effects were weak and emerged in RTs and error rates depending on whether left or right M1 was stimulated. Conclusions: Our results confirm the potential of this novel HD-tDCS set-up to modulate behavioural performance in a regionally specific manner. Selectively improved conflict adaptation during DLPFC stimulation supports the theory that left and right DLPFC play a critical role in behavioral adaptation following conflict detection.